Development and Application of Android Based Mobile Optical Test Reading System [Android Tabanli Mobil Optik Test Okuma Sisteminin Geliştirilmesi ve Uygulamasi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
In this study, a mobile-based optical reading system was developed for the rapid evaluation of educational processes. Optimization of the optical reading process was aimed with the mobile application developed. It takes time to evaluate the results of multiple choice test exams. The results of the existing systems were evaluated by analyzing the deficiencies. A reliable and open to development system was designed. A photo of the exam paper was taken with the camera of an android phone and transferred to the developed mobile application. Response options and student numbers were read. In the light of the obtained data, student, teacher and exam information were transferred to the database. Reports could be obtained with this information at any time in the online environment. The optimum amount of light that provides the most ideal reading of the optical form was determined as a result of the measurements. With the application with a user friendly interface, it was seen that successful results were obtained in the photos taken with a right angle and greater than 50 lumens of the ambient light without being connected to a separate device. © 2020 IEEE.
Keywords: Image processing; optical paper reading